2011
DOI: 10.1111/j.1751-9020.2011.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

African‐American Women and Suicide: A Review and Critique of the Literature

Abstract: This paper reviews the literature on African‐American women’s suicide rates. This topic is often neglected due to African‐American women’s low rates of suicide occurrence. This review seeks to answer the call for increased scientific inquiry on matters related to African‐American women and suicide. The author begins by identifying complex dynamics surrounding African‐American women’s unique social position in order to establish a better understanding of how socio‐cultural influences are addressed in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Although there is an emerging body of research on religious participation and psychological disorders, this is the first paper on religious participation and DSM-IV MDD among a national sample of African Americans. The findings are consistent with previous research on both African Americans (Chatters et al, 2008, 2009; Ellison et al, 2008; Krause, 2008; Spates, 2011; Tabak & Mickelson, 2009; Taylor et al, 2007) and whites (George, 2011; Koenig et al 1994; McCullough & Larson, 1999; Smith et al, 2003) which shows that religious participation is a protective factor for mental health and mental illness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although there is an emerging body of research on religious participation and psychological disorders, this is the first paper on religious participation and DSM-IV MDD among a national sample of African Americans. The findings are consistent with previous research on both African Americans (Chatters et al, 2008, 2009; Ellison et al, 2008; Krause, 2008; Spates, 2011; Tabak & Mickelson, 2009; Taylor et al, 2007) and whites (George, 2011; Koenig et al 1994; McCullough & Larson, 1999; Smith et al, 2003) which shows that religious participation is a protective factor for mental health and mental illness.…”
Section: Discussionsupporting
confidence: 92%
“…Further, given characteristically high levels of religious behaviors and coping strategies (Bediako et al, 2010; Chatters et al, 2008, 2011; Krause & Chatters, 2005; Taylor & Chatters, 2011; Taylor et al, 2004) within this group, the effect of religion on depression and other mental health outcomes may be especially robust (Chatters et al, 2008, 2009; Krause 2008; Spates, 2011; Tabak & Mickelson, 2009; Taylor et al, 2007). Although religious involvement is generally beneficial for psychosocial and mental health outcomes among African Americans (Chatters et al, 2008, 2009; Ellison et al, 2008; Krause, 2008; Spates, 2011; Tabak & Mickelson, 2009; Taylor et al, 2007), only a few studies specifically examine the association between religious involvement and depression (i.e., depressive symptoms, MDD). In a series of studies, Brown (Brown & Gary, 1985; Brown et al, 1990) and colleagues found that depressive symptoms were inversely related to religious involvement (e.g., attendance and affiliation) (Brown & Gary, 1994).…”
Section: African Americans Religion and Depressionmentioning
confidence: 99%
“…Experiencing IPV leads to an increase in depressive symptoms, which is associated with higher levels of suicidal ideation among low-income, African American women (Leiner, Compton, Houry, & Kaslow, 2008). African American women are more susceptible than women from other ethnic/racial background to depression (McKnight-Eily et al, 2009) and untreated depression is a risk factor for suicidal behavior in this population, as well as in other ethnic/racial groups (Spates, 2011). …”
Section: Ipv Suicidality and Depressive Symptoms In Low-income Afrmentioning
confidence: 99%
“…In their investigation of race, trauma, and suicide attempts, O’Hare, Shen, and Sherrer (2016) found that past trauma and posttraumatic stress disorder were associated with suicide attempts among Hispanics but not African Americans. Despite experiencing some of the highest levels of depression, trauma, and psychological distress, African American women persistently have had the lowest rates of suicide in the United States and throughout the world (Kaslow et al, 2000; Spates, 2011). Few studies, however, have explored how culture and culture-specific coping strategies among African Americans may influence their suicidal behavior.…”
mentioning
confidence: 99%